The world bank and politization of its mandate (2007)
This article asserts that, as a result of the rule program adopted by the World Bank at the beginning of the nineties, the institution has assumed a politicization of its mandate taken as the legitimization of deeper intervention in the restructuring of economic and political roles by moneylender states. Such politicization has been backed in an ad hoc reinterpretation of the founding statutes, allowing wide institutional intervention in diverse affairs previously considered strictly political. By proceeding this way, the bank has clearly broken the intended technical character featured since its foundation in the second post war.